(untitled) (Architecture Image Studies, 2025)
This paper entitled “Bridging the Gap: A Systematic Deconstruction Strategy for ESL Student Success in Academic Writing” puts forward a strategy for writing prompts, tailored to help English as a Second Language (ESL) for students to navigate the challenges of academic writing. Since academic writing is fundamental in education, ESL learners experience untoward obstacles due to the linguistic and cultural subtleties in the assigned tasks. The technique proposed simplifies abstract instructions into concrete manageable steps by breaking them down into small chunks of understandable pieces. In a straight forward way, it addresses both rhetorical and disciplinary requirements to build confidence among students and accuracy across variegated writing tasks. The paper emphasises on the emerging field of prompt engineering, highlighting its significance in enabling students to use AI tools effectively and efficiently for multiple purposes like learning, research, and the development of critical thinking skills. It brings to light the pivotal role of English Language Teachers (ELTs) in nurturing these abilities by emphasising on clarity, contextual understanding and ongoing refinement. O.Henry’s “The Gift of the Magi” is used as a practical example to demonstrate the strategy of enhancing language proficiency and critical thinking, with the aim of preparing ESL students to make them competent for the demands of academic discourse and professional environments in an AI-driven world.